scRNA+TCR-seq reveals the pivotal role of dual receptor T lymphocytes in the pathogenesis of Kawasaki disease and during IVIG treatment - Xu, Yuanyuan; Yuan, Yi; Mou, Lanlan; Hui, Linhu; Zhang, Xing; Yao, Xinsheng; Li, Jun (Frontiers in Immunology, 2024)
Introduction：Kawasaki disease (KD), a common cause of acquired heart disease in children in developed countries, is primarily treated with intravenous immunoglobulin (IVIG), but some children demonstrate IVIG resistance with increased coronary artery injury risk. T cells have been demonstrated to be involved in the pathogenesis of KD and its treatment with IVIG. However, the role and mechanism of dual TCR T lymphocytes in the occurrence of KD and IVIG therapy remain unclear.Methods:This study, based on scRNA-seq combined with TCR-seq technology, clustered the peripheral blood mononuclear cells of 3 healthy controls and 6 KD patients before and after IVIG treatment.Comparative analysis was conducted to investigate the differences in the proportion of single/dual receptor T cells, the characteristics of CDR3 repertoires, cell types, and the expression of transcription factors among the three groups. The study aimed to explore the correlation between dual TCR T cells and KD as well as IVIG treatment.Results：In our experimental results, we observed the presence of dual TCR T cells in all three groups.However, compared to the healthy control group and the IVIG-treated 2 group, the KD patients before IVIG treatment exhibited a lower proportion of dual TCR T cells, with variability between samples, ranging from 4% to 15%. Notably, after IVIG treatment, the proportion of dual TCR T cells significantly increased, stabilizing above 12%, and these T cells also exhibited clonal expansion and a preference for V gene usage.In addition we found differences in dual TCR T cell subsets among the three groups, for example,IVIG treatment increases the proportion of dual TCR Treg cells, but it still remains below that of healthy control groups, significantly higher proportions of both dual TCR CD8 central and effector memory T cells in IVIG-treated KD patients, and differences in the expression of transcription factors between single and dual TCR T cells. These results suggest dual TCR T cells correlate with KD and IVIG treatment.:Dual TCR T lymphocytes, especially dual TCR CD8 T cells and Treg cells, play crucial roles in the pathogenesis of KD and during IVIG treatment, providing strong support for further elucidating KD pathogenesis and optimizing treatment strategies.